2015
DOI: 10.5430/ijfr.v7n1p121
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Oil and Stock Prices Comovements

Abstract: The dynamic relationships between crude oil prices, oil sector stock price indices and stock market price indices is examined and evidence of cointegration between these variables is found. A vector error-correction (VEC) model reveals that the stock prices of companies in the integrated oil and gas sector have a long-run negative relationship with oil prices while those in the oil and gas exploration and production sector have a long-run positive relationship with oil prices. Both indices have a long-run rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, some studies examined negative association between inflation rate and stock returns (e.g., Ratti, Vespignani 2016;Haugom et al 2016;Jiang, Gu 2016;Albulescu et al 2016;Mushtaq 2012;etc.). Several studies investigated the affects of interest rate and inflation rate on equity returns, and concluded that inflation and interest rate have an inverse association on stock returns (e.g., Gomes 2015;Sultonov 2015;Gilmore et al 2015;etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies examined negative association between inflation rate and stock returns (e.g., Ratti, Vespignani 2016;Haugom et al 2016;Jiang, Gu 2016;Albulescu et al 2016;Mushtaq 2012;etc.). Several studies investigated the affects of interest rate and inflation rate on equity returns, and concluded that inflation and interest rate have an inverse association on stock returns (e.g., Gomes 2015;Sultonov 2015;Gilmore et al 2015;etc. ).…”
Section: Discussionmentioning
confidence: 99%